CRITERIA FOR TOBACCO IDENTIFICATION FOR HOOKAH AND NON-TOBACCO MIXTURE FOR HEATING - M. V. Shkidyuk; S. V. Gvozdetskaya; O. K. Bedritskaya; G. P. Shuraeva (Новые технологии)
Hookah tobacco is positioned as a “nicotine alternative” to traditional smoking, but the aerosol produced contains the same toxic components as cigarette smoke.Consumer properties and safety indicators of tobacco aerosol for hookah depend on the component composition of the tobacco mixture and the coal used. The main factor that has a physiological effect on the user of hookah tobacco or non-tobacco mixture for heating is the content of nicotine that passes into the aerosol.There is no single approach to the regulation of a segmental product, in addition, there are no standardized methods for generating and collecting aerosol. The smoking pattern on a laboratory smoking machine does not fully reflect the behavioral profile of a person, however, the quantitative composition of the aerosol obtained from machine testing can be used as input to determine the risk of the product.During the research, laboratory and analytical equipment was used: CERULEAN SM 405 linear smoking machine; "Expert-001-1(0.1)" ionomer, SF-16 spectrophotometer, Crystal 2000M / HP 5890 Series 11 chromatograph with FID.Experimental data have been obtained to evaluate consumer and physic-chemical parameters, including organoleptic evaluation, the content of nicotine, glycerin and propylene glycol in samples of tobacco for hookah / non-tobacco mixture for heating.The method of machine generation and collection of the solid-liquid phase of an aerosol has been standardized, which makes it possible to obtain reliable data on the quantitative content of nicotine in the produced aerosol. The content of nicotine in the samples is 0.1–1.9%, the transition of nicotine into the produced aerosol is insignificant.The microscopy method for determining the structure of the base (carrier) in combination with the determination of consumer properties (organoleptic evaluation, total content of glycerol and propylene glycol, pH and nicotine content) are tools for identifying tobacco or non-tobacco hookah products.